Dung beetle richness decreases with increasing landscape structural heterogeneity in an African savanna‐agricultural mosaic. Issue 4 (26th February 2018) - LaScaleia, Michael C.; Reynolds, Chevonne; Magagula, Cebisile N.; Roets, Francois; McCleery, Robert A.
Abstract: The landscape heterogeneity hypothesis posits that increasing variance of land cover types in agricultural landscapes will increase landscape level biodiversity. This hypothesis, however, does not detail which component of landscape structural heterogeneity, compositional (the type and amount) or configurational (the shape and arrangement) has the greatest influence on biodiversity and at what spatial scale(s). We investigated how dung beetle (Scarabaeidae) alpha‐diversity responded to landscape structural heterogeneity at a variety of spatial scales in an agricultural mosaic‐landscape in north‐eastern Swaziland. We also compared the effect of these components to the effect of variation in the amounts of major land‐cover types in the landscape and plot level vegetation structure. We used pitfall traps to sample the dung beetle community along a gradient of heterogeneity and used linear mixed effects models to compare the effect of each component on dung beetle richness and Shannon diversity at four separate spatial scales (i.e. 1‐, 1.5‐, 2‐ & 3‐km). Land‐cover diversity and number of patches represented compositional and configurational landscape heterogeneity respectively. Landscape compositional heterogeneity was negatively correlated with dung beetle richness at the 1.5‐km and 2‐km spatial scales. The percentage savanna in the landscape was positively correlated with dung beetle richness at the 3‐km and 2‐km scales. Landscape level heterogeneity may enhance diversity of some taxonomic groups, but this was not the case for dung beetles in a southern African savanna. The best way to maintain their diversity is to create or maintain large continuous blocks of savanna while limiting intensive agriculture.